PERBEDAAN ASUPAN ZAT GIZI PASIEN HEMODIALISA DI RSUD dr. DORIS SYLVANUS PALANGKA RAYA - dewi, fretika utami (Program Studi Ilmu Gizi, Jurusan Kesmas Fakultas Ilmu-Ilmu Kesehatan Universitas Jenderal Soedirman, 2018)
ABSTRACT Background: Hemodialysis is a catabolic process (breakdown of complex compounds into simpler compounds) in which amino acid removal and protein synthesis depletion occurred. Objective: To investigate differences in nutritional intake of hemodialysis patients at RSUD dr. Doris Sylvanus Palangka Raya. Research Methodology: This research is an observational research with Pre-post design. Purposive sampling technique was employed on 13 PGK patients who undertake weekly hemodialysis at RSUD dr. Doris Sylvanus Palangka Raya. Data of protein, sodium, potassium and oral intakes were obtained by interview and 24-hour food recall for 2 consecutive days of pre and post hemodialysis. BM photo book was used during interview and food recall. Data were analyzed using paired t-test. Result of the study: Most of samples were female (92%), ranged at 46-67 years old, graduated from elementary school and not working. Bivariate test showed p value of protein, sodium, potassium and fluid intakes were 0.022, 0.382, 0.075 and 0.836, respectively. Hemodialysis aims to restrain uremia, excessive fluid and electrolyte imbalance that occur in end-stage renal failure patients. Hemodialysis may increase survival rate of patients as it is effectively removing fluids, electrolytes and metabolites. Conclusion: There was a significant difference in protein intake and insignificant differences in sodium, potassium and fluid intakes of pre and post hemodialysis patients at RSUD dr. Doris Sylvanus Palangka Raya.